2011
DOI: 10.1152/japplphysiol.00907.2010
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial metabolic adaptations due to endurance exercise training in the fasted state

Abstract: Training with limited carbohydrate availability can stimulate adaptations in muscle cells to facilitate energy production via fat oxidation. Here we investigated the effect of consistent training in the fasted state, vs. training in the fed state, on muscle metabolism and substrate selection during fasted exercise. Twenty young male volunteers participated in a 6-wk endurance training program (1-1.5 h cycling at ∼70% Vo(₂max), 4 days/wk) while receiving isocaloric carbohydrate-rich diets. Half of the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
191
0
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(219 citation statements)
references
References 54 publications
8
191
0
20
Order By: Relevance
“…In this regard, we and others have collectively observed that reducing endogenous and/or exogenous CHO availability during short-term (e.g. 3-10 week) endurance training increases mitochondrial enzyme activity and protein content [55,59,60] increases both whole body [55] and intramuscular lipid oxidation [61] and in some instances, improves exercise capacity [62,63]. These data have therefore led to the innovative "train-low (or smart), compete-high" model surmising that athletes deliberately complete a portion of their training programme with reduced CHO availability so as to augment training adaptation but yet always ensure high CHO availability prior to and during competition in an attempt to promote maximal performance [64].…”
Section: Is Carbohydrate Still King?mentioning
confidence: 80%
See 1 more Smart Citation
“…In this regard, we and others have collectively observed that reducing endogenous and/or exogenous CHO availability during short-term (e.g. 3-10 week) endurance training increases mitochondrial enzyme activity and protein content [55,59,60] increases both whole body [55] and intramuscular lipid oxidation [61] and in some instances, improves exercise capacity [62,63]. These data have therefore led to the innovative "train-low (or smart), compete-high" model surmising that athletes deliberately complete a portion of their training programme with reduced CHO availability so as to augment training adaptation but yet always ensure high CHO availability prior to and during competition in an attempt to promote maximal performance [64].…”
Section: Is Carbohydrate Still King?mentioning
confidence: 80%
“…As such, many challenges remain as to how best to periodise train-low into an elite athlete's training programme without increasing the risk of the aforementioned maladaptive responses. At present, research studies examining the efficacy of train-low strategies have largely adopted fasted training protocols [60], protein only sessions [70], training twice per day models [62] reducing CHO intake in the post-exercise period [71] and most recently, both sleeping and training (i.e. sleep low-train low models) on the subsequent morning with reduced CHO intake [21,72].…”
Section: Is Carbohydrate Still King?mentioning
confidence: 99%
“…Furthermore, the fasting endurance-training program also stimulated net IMCL degradation in type IIa muscle fibers during exercise (64). It is reasonable to conclude that exercising with lowcarbohydrate availability is an effective strategy to promote fat oxidation rate by enhanced IMCL breakdown in endurance exercise (37,64,70). This conclusion is supported by studies showing increased ␤-HAD activity as well as protein content or elevated activity of citrate synthase and succinate dehydrogenase following training in a carbohydrate-depleted state (26,37,48,64,70).…”
mentioning
confidence: 85%
“…We also demonstrated that consistent training in F can increase membrane-bound fatty acidbinding protein and FAT/CD36 protein content in muscles more than an identical training program with ample carbohydrate intake (CHO) during the training sessions (16a). Furthermore, the fasting endurance-training program also stimulated net IMCL degradation in type IIa muscle fibers during exercise (64). It is reasonable to conclude that exercising with lowcarbohydrate availability is an effective strategy to promote fat oxidation rate by enhanced IMCL breakdown in endurance exercise (37,64,70).…”
mentioning
confidence: 93%
See 1 more Smart Citation